The Entity between Light and Lamp Epistemological Study of the Problems of the Text and the Plurality of Reading In the Linguistical Modern Lesson - Jabbar Kadhem Dawood Al-Omairi, Emad (Journal of College of Education, 2019)
The difference in the grasp of the subject of the text ,the concept and the limit does not mean, in my conception, that it is a preoccupation with no values, or a call without purpose, but rather the engagement and expansion of the knowledge the in a centralized of the entity that fragmentizes on orbits of human history, translated by different signals, signs and connotations in the light of value systems. If knowledge proceeds from a circle that shares a manifestation and an atrophy of a subject, from entity , thing and a relationship in a way that is spaced and convergent, then it is perceived, practiced, communicated, acted and intended - according to the reference of “who knew himself” - it inevitably seems to be shining and meaningful in all joints of existence, and the text is in it and to it in the way that it is a clarity and clarification, which, necessarily, witnessed in looking and reading, thought and interpretation.